Pemanfaatan Nutrisi Ayam Petelur Fase II (55 Minggu) Dengan Pemberian Pakan Free Feeding Choice - Moch Tirta Ageng Bambang Priomojo; Eudia Christina Wulandari; Purwadi Purwadi (Tropical Animal Science, 2021)
The purpose of this study was to look at the utilization of phase II laying hens nutrition by giving Free Feeding Choice feed. The material used in the study was 30 Brown Leg Horn laying hens with the age of 55 weeks. In this study, the use of the free-choice technique of feed with corn, finished concentrate, rice bran, and premix as feed ingredients. The parameters of this study were ration consumption, Hen Day Production, egg weight, digesta rate, and crude fiber digestibility. The results showed that the treatment had a significant effect, the average feed consumption of laying hens was 114 grams/day. Average production reaches 95%. The average overall weight is 65.15 grams. The average digestibility value of crude fiber was highest in the T10 treatment, which was 42.26% and the lowest in the T19 treatment 4.37%. The highest crude fiber consumption was T10 18.08% and the lowest was T13 6.11%. From the results of the research that has been done, it can be concluded that layer II brown leg horn laying hens with Free Feeding Choice feeding provide an opportunity for chickens to choose the feed ingredients needed to produce eggs.